2015
DOI: 10.1111/joim.12402
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary rehabilitation treatment versus cognitive behavioural therapy for patients with chronic fatigue syndrome: a randomized controlled trial

Abstract: Objectives. The aim of this trial was to evaluate the difference in treatment effect, at 26 and 52 weeks after the start of treatment, between cognitive behavioural therapy (CBT) and multidisciplinary rehabilitation treatment (MRT) for patients with chronic fatigue syndrome (CFS).Design. Multicentre, randomized controlled trial of patients with CFS. Participants were randomly assigned to MRT or CBT.Setting. Four rehabilitation centres in the Netherlands. Subjects. A total of 122 patients participated in the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
65
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 42 publications
1
65
0
2
Order By: Relevance
“…This study is part of the FatiGo trial, a multi-centre, pragmatic twoarm randomized controlled trial (ISRCTN77567702) of which the methods and results are described previously [3,4]. The main aim of the FatiGo trial was to analyse the difference in treatment effect between MRT and CBT for patients with CFS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is part of the FatiGo trial, a multi-centre, pragmatic twoarm randomized controlled trial (ISRCTN77567702) of which the methods and results are described previously [3,4]. The main aim of the FatiGo trial was to analyse the difference in treatment effect between MRT and CBT for patients with CFS.…”
Section: Methodsmentioning
confidence: 99%
“…Results of the randomized trial comparing MRT and CBT showed that immediately post-treatment (26 weeks after start of treatment) both treatments showed significant reduction of fatigue and increase of quality of life, however the between group differences were not significant. At 52 weeks follow-up, MRT was more effective in reducing fatigue and equally effective in improving quality of life [4]. To understand the working mechanisms of these interventions and to find out how to increase their effectiveness, it is important to study factors that influence the outcome of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of innovation in the field of ME/CFS rehabilitation has somewhat slowed over the past few years or even decades. However, in this issue of the Journal of Internal Medicine, Vos-Vromans et al report an innovative study showing that interdisciplinary rehabilitation is more effective than cognitive behavioural therapy in reducing fatigue for patients with ME/CFS [5].…”
mentioning
confidence: 99%
“…The idea of 'blurred boundaries' between healthcare professions leads to the issue of to what extent different disciplines are required to deliver the intervention described by Vos-Vromans et al [5]. The interdisciplinary team consisted of an occupational therapist, physiotherapist, social worker and psychologist.…”
mentioning
confidence: 99%
See 1 more Smart Citation